Service - Oriented Organisational Citizenship Behaviour In Malaysian Upscale Hotels: The Role Of Organisational Resources, Job Resources, Personal Resources, And Work Engagement - Choo, Ling Suan (2014)
Service - Oriented organisational citizenship behaviour (SO-OCB) is a form of extra-role behaviour that goes beyond formal work descriptions in a service organisation. Consisting of three dimensions, loyalty OCB, service delivery OCB, and participation OCB, SO-OCB is important to service organisations, such as hotels in improving its service quality and customer loyalty. This study grounded in the Conservation of Resources Theory', posited a positive and significant relationship between three bases of resources (organisation, job. and personal) and SO-OCB.